PENGENALAN CERITA RAKYAT I GEDE BASUR MELALUI CERITA BERGAMBAR BERBASIS ANDROID - Ni Putu Setia Dewi; I Ketut Setiawan (Jurnal Nawala Visual, 2020)
The loss of storytelling tradition makes children forget about folktales, whereas folktales contain many positive values about norm, ethics, and moral character. In the middle of technology development nowadays, it needs synergy between local wisdom with technology so that both can walk hand in hand and support each other. Considering that children become “close” with their smartphone, thus to introduce folktales to the children with modern medium, comic strip (cergam) based on digital android is designed. The folktales being used is taken from the story by I Gede Basur, where in the story contains a moral message about cause and effect law, the bad will always be defeated by the good, we should not be arrogant, filial to parents and work hard.Data collection method used in this research is observation related to the development of smartphone usage by children. Questionnaire to know the types of characters, and whatever the children do with their smartphone.Literature method is used to obtain information about narration and plot of the story from I Gede Basur’s folktales.The research resulted in a digital comic strip based on android which consists of 3 parts, namely introduction, content, and closure. The comic strip is made with the concept of happiness, with cartoonal visualization style and light color, combined with animation, and sound effect to make the comic strip become interesting to be read by children.